كاردانەوەی ئەنفال لە ئەدەبدا (شیعر- چیرۆك - ڕۆمان) (لێكۆڵینەوەیەكی ڕەخنەیی شیكارییە) - سەعید, محەمەد ئەحمەد; عومەر, مەهدی فاتیح (Sulaimani Journal for Humanities, 2018)
In the his paper، The Implications of Al-Anfal in Literature، the researcher attempts to shed light on the status of Kurdish literature and its readiness to approach the tragedy caused by this event— Al-Anfal. The study investigates this topic in a general way and does not tend to evaluate all literary genres –poetry، short story، and novel- that have reflected this tragedy nor does it claim approaching the poets or writers who dealt with it in their literary products . The paper is made up of two sections. The first section، Anfal and the Dominant Status of Kurdish Literature، highlights the main characteristics of Kurdish literature، but with a light critical 14 review. In the second section، Anfal and Literature: Identifying the nature of their relationship، the researcher tackles the types of implication of Anfal and its use in Kurdish literary texts. In the conclusion، the aim that the study has worked to fulfill has been attained. The paper has actually aimed at criticizing the odd the implications of Anfal and misusing this tragic event، and tried to create a sound relationship between literature and Anfal. Also، the study ends with a list of the references used and an abstract in both Arabic and English.